The Effect of Liquidity and Solvability on the Profitability of Banking Companies Listed on the Indonesia Stock Exchange in 2017-2019 - Tiara Rizky Miftachul Jannah; Mursidi Mursidi; Widayat Widayat (Universitas Muhammadiyah Malang, 2021)
The purpose of this study was to determine the effect of liquidity and solvability on the profitability of banking companies listed on the Indonesian stock exchange for the 2017-2019 period. The population used in this study is data on loan to deposit ratio, debt to, capital adequacy ratio, and ROA. The sample taken is data from the 2017-2019 period as many as 28 banking companies. The data analysis technique in this study uses multiple linear regression, while the analytical tool used is SPPS version 25. The results of this study state that the projected liquidity variable with the loan to deposit ratio has no significant effect on company profitability. The solvability variable projected by the capital adequacy ratio has no significant effect on the company's profitability. The liquidity variable projected by the loan to deposit ratio, and the solvability variable projected by the capital adequacy ratio simultaneously do not affect the company's profitability, and the most influential variable on profitability is solvability projected by the capital adequacy ratio (CAR).